Observational Analysis of the Effectiveness of Entrepreneurship Training Programme in Rural Development and Self Employment Training Institutes (RUDSETI) (Indian Journal of Extension Education, 2020)
There have been a plethora of organizations involved in entrepreneurship development training, however, the way training is conducted has always been a concern to stakeholders. To assess the effectiveness of one institution directly dealing with entrepreneurial training (RUDSETI), a holistic approach was employed through a combination of methods. Participant observation was done during entrepreneurship training as well as administered knowledge test and sought feedback from trainees on various facets of training. Results showed that the duration of the training was perceived insufficient (3.8) for trainings with much practical sessions. The subject matter was covered near to completely (4.2) and there was a sequential presentation of topics (4.5). Eye contact was maintained throughout the training (4.2). There was 45 per cent increase in knowledge of the trainees as a result of the training. Majority of the trainees rated the training effectiveness above 80 percent. The overall effectiveness index was 84 per cent.